The Use of 3D Learning Media in Stimulating Motor and Cognitive Development in Early Childhood: An Islamic Education Perspective - Rani Dwi Lestari; Syafrimen Syafril (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Three-dimensional learning media are increasingly being used in early childhood education due to their ability to provide concrete and multisensory learning experiences. From an Islamic educational perspective, the use of these media not only contributes to cognitive development but also has the potential to integrate spiritual values into the learning process. This study aims to analyze the characteristics and synthesize findings regarding the use of three-dimensional learning media in stimulating the fine motor and cognitive development of early childhood from an Islamic educational perspective. The method used is a Systematic Literature Review (SLR) of 170 articles published between 2020 and 2025, employing thematic analysis. This study employed a Systematic Literature Review method by identifying 1,097 articles from Scopus and Sinta spanning the years 2020–2025 through a structured selection process, resulting in 15 articles that were analyzed using a thematic approach. The research findings indicate that three-dimensional learning media promote multisensory learning experiences that enhance children’s active exploration, hand-eye coordination, attention to detail, and logical thinking skills. Furthermore, the use of these media supports the integration of Islamic values through reflective and contemplative learning. Overall, three-dimensional media contribute to a holistic learning approach that integrates children’s physical, cognitive, and spiritual development. This study offers practical implications for early childhood educators and parents in designing three-dimensional media-based learning activities integrated with Islamic values, and points the way toward the development of more innovative and holistic learning models.